Biodiversidade dos parasitas de peixes provenientes do rio Sapucaí-Mirim, Estado de São Paulo, Brasil - Zago, Aline Cristina [UNESP] (2016)
Recently, parasites have been recognized as important components of global biodiversity because the important roles played by these organisms in natural ecosystems. Although knowledge about the diversity of parasites has increased in recent decades, the number of parasite species of fishes in Brazil is relatively low compared to the biodiversity of host species. Thus, this study aimed to survey the biodiversity of fish parasites from four sampling sites in an area under the influence of Small Hydroelectric Power Plants in the Sapucaí-Mirim River, São Paulo State, Brazil, as well as to evaluate the structure of metazoan parasite communities of Characiformes and four species of Leporinus sp. From March 2012 to July 2013, 462 fish specimens of 16 species of Characiformes, Siluriformes, Perciformes, and Gymnotiformes were collected. It was observed that 86.58% of fish specimens were parasitized by at least one metazoan parasite taxon. The parasites found belonged to eight different groups (Myxozoa, Monogenea, Digenea, Cestoda, Nematoda, Acantocephala, Arthopoda and Annelida) and a total of 6,830 parasites were collected and analyzed. Ninety-seven parasite taxa were found, and Monogenea was the group that had the highest number of species, followed by Nematoda and Digenea. The parasite communities of Characiformes showed mainly differences among the host species, although belonging to the same order or family. The sampling site, condition factor and the host body size also influenced the distribution of parasite abundance of some fish species analyzed. The metazoan parasite communities of Leporinus spp. primarily showed differences among the host species, wherein the infracommunities of Leporinus amblyrhynchus and Leporinus elongatus tended to be more similar, as well as Leporinus friderici and Leporinus octofasciatus. New locality records are made to all parasite species collected and were also found new parasite species and are made new occurrence records on different hosts for several parasite species.